Study the Genetics of the Important Yield Attributing Traits and Identification of Potential Germplasm of Brinjal (Solanum melongena L.) - Dumi, Taru; Neresha, Wakrambam; Golay, Sangay; Barman, Animesh; Sikder, Subhamoy; Basfore, Shibnath; Chatterjee, Ranjit (International Journal of Bio-resource and Stress Management, 2025)
Present experiment was conducted during October–April of 2021–22 and 2022–23 under the Department of Vegetable and Spice Crops, Uttar Banga Krishi Viswavidyalaya, Cooch Behar, West Bengal using forty-two brinjal germplasm on ten yield attributing traits to study the inheritance pattern for crop improvement. Experiment was laid out in RBD and pooled data of two years were subjected to statistical analysis. Negligible difference among GCV and PCV for all the traits excepting yield and pedicel length indicated that there was less environment influence. Existence of high heritability coupled with genetic advance for all the traits indicated existence of additive gene action in their inheritance. Character association and path coefficient revealed that fruit diameter, fruits inflorescence-1, inflorescence plant-1, fruit length and fruit weight could be considered effective traits as a basis for selection. Principle factor analysis broadly categorised all the traits into three groups those cumulatively explained 74.74% of the variance where first factor (38.2%) represented by flowers inflorescence-1 (0.739), inflorescences plant-1 (0.877), fruits inflorescence-1 (0.885), fruits plant-1 (0.871) and fruit weight (-0.602); Second factor (20.04%) was explained by plant height (0.876), fruit length (0.765) and pedicel length (0.876); third factor (16.50%) was associated with fruit diameter (0.767), fruit weight (0.738) and yield hectare-1 (0.859). 2021/BRLVAR-9, Pundibari Chikon, Utkal Kesari, Utkal Anushree, Hija were considered most suitable for selection of narrow and multi fruited germplasm and 2019/BRLVAR-9, 2020/BRRVAR-2, 2019/BRRVAR-1, 2019/BRRVAR-7, 2019/BRRVAR-13 and Nawabganj were considered most suitable for selection of big sized and high yielding germplasm.